Taxonomic revision of the Neotropical genus Heteragrion Selys, 1862 (Zygoptera: Heteragrionidae): male morphology, new species and illustrated key - Vilela, Diogo Silva; Lencioni, Frederico A. A.; Bota-Sierra, Cornelio A.; Ware, Jessica L.; Bispo, Pitágoras C. (Zootaxa, 2023)
In this study, we have comprehensively presented taxonomic information on all 62 known species of Heteragrion Selys, 1862, which includes illustrations, photographs, diagnostic characters, and a key to males. Our analysis is based on the examination of over 900 specimens from 19 different collections worldwide, encompassing the type material for at least 42 species. Furthermore, we have described a new species, Heteragrion corderoi sp. nov. (♂, BRAZIL, São Paulo state, Campos do Jordão, Condomínio Paradise, 24.i.1999, (Coordinates: -22.7072, -45.5894, 1796 m asl), F.A.A. Lencioni leg., LABECO), which we identified from a male that was previously considered to be a paratype of H. mantiqueirae Machado, 2006 and additional specimens collected in Campos do Jordão, São Paulo state.